EPIRETINAL FIBROSIS REMOVAL IN AN ARGUS II–IMPLANTED EYE: Histological Characteristics and Functional Results. Issue 12 (December 2020) - Patelli, Fabio; Falleni, Monica; Colombo, Leonardo; Martinelli, Carla; Tosi, Delfina; Bulfamante, Gaetano; Rossetti, Luca
Abstract : Purpose: 1) To investigate morphologic and histochemical characteristics of an epiretinal fibrosis removed in an Argus II–implanted eye; 2) to evaluate the Argus II function before and after the fibrosis removal, and 3) to compare morphologic and functional data. Methods: Fibrosis, which developed between the Argus II prosthesis and the retina two years after implant, was surgically removed. Its morphologic and histochemical characteristics were evaluated both in light and transmission electron microscopy, with special stains and immunohistochemistry. The Argus II function was evaluated during the follow-up before surgical removal and 1 month later. Results: Fibrosis was successfully removed. It was composed of a fibrotic tissue with spindle cells arranged in nodular aggregates with a symmetric distribution, mixed with an inflammatory infiltrate. Extra- and intracellular, irregular, small iron particles were found and confirmed ultrastructural characterization with degenerative cellular changes. The repositioned Argus II restored, and its function was partially nearly to normal values 1 month after surgery. Conclusion: Fibrosis can develop between the Argus II and the retina with increasing reduced function. Morphologic characteristics of the removed fibrosis suggested a pathogenesis based on an inflammatory process involved in a foreign body reaction with progressing connective tissue deposition leading to sclerosis. Adequate clinical follow-up is critical to successful removal of the fibrosis with reactivation of the Argus II function. Abstract : An epiretinal fibrosis, which developed between the Argus II and the retina with increasing reduced function, was surgically removed. Morphologic characteristics of the removed fibrosis was studied and suggested a pathogenesis based on an inflammatory process involved in a foreign body reaction with progressing connective tissue deposition. After surgery, reactivation of the Argus II function was noted.